2019
DOI: 10.1136/bmjopen-2019-032659
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and acceptability of cognitive–behavioural therapy based interventions for maternal peripartum depression: a systematic review, meta-analysis and thematic synthesis protocol

Abstract: IntroductionPeripartum depression is a common mental health difficulty associated with a range of negative impacts for the mother, infant and wider family. This review will examine the effectiveness of cognitive–behavioural therapy (CBT) based interventions for peripartum depression. Secondary aims are to explore the effect of CBT-based interventions targeted at peripartum depression on novel secondary outcomes and moderators potentially associated with effectiveness. To date, there has been little examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…The review protocol is published [24] and registered in PROSPERO (CRD 42020152254). Methods are informed by Cochrane guidance [37], the Centre for Reviews and Dissemination guidance [38], and reporting follows the PRISMA 2021 statement [39] (Additional file 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The review protocol is published [24] and registered in PROSPERO (CRD 42020152254). Methods are informed by Cochrane guidance [37], the Centre for Reviews and Dissemination guidance [38], and reporting follows the PRISMA 2021 statement [39] (Additional file 1).…”
Section: Methodsmentioning
confidence: 99%
“…Another limitation of the existing evidence base is that a number of important secondary outcomes have been largely unexamined [ 24 ], for example, anxiety, stress (individual and perceived parenting), parenting (e.g., sensitivity/responsiveness), perceived social support, and perceived parental competence. Given high comorbidity rates of PND and anxiety [ 4 ], the impact of stress on both mothers and the infant [ 28 , 29 ], the association between PND and parenting difficulties [ 7 ], and poor social support [ 30 ], it is suggested that PND interventions should also try to improve these important outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some women, particularly those with mild and moderate symptoms of depression, will benefit from therapeutic modalities like Cognitive Behavioral Therapy (CBT) and Interpersonal Therapy (IPT; Letourneau et al, 2017;Pettman et al, 2019;Sockol, 2015), others require pharmacologic intervention to control symptoms. As a result, there has been increasing interest in determining the safety of psychotropic treatment in pregnancy.…”
mentioning
confidence: 99%